Looming Effects on Attentional Modulation of Prepulse Inhibition Paradigm - Wu, Zhemeng; Bao, Xiaohan; Liu, Lei; Li, Liang (Frontiers in Psychology, 2021)
In a hazardous environment, it is fundamentally important to successfully evaluate the motion of sounds. Previous studies demonstrated “auditory looming bias” in both macaques and humans, as looming sounds that increased in intensity were processed preferentially by the brain. In this study on rats, we used a prepulse inhibition (PPI) of the acoustic startle response paradigm to investigate whether auditory looming sound with intrinsic warning value could draw attention of the animals and dampen the startle reflex caused by the startling noise. We showed looming sound with a duration of 120 ms enhanced PPI compared with receding sound with the same duration; however, when both sound types were at shorter duration/higher change rate (i.e., 30 ms) or longer duration/lower rate (i.e., more than 160 ms), there was no PPI difference. This indicates that looming sound–induced PPI enhancement was duration dependent. We further showed that isolation rearing impaired the abilities of animals to differentiate looming and receding prepulse stimuli, although it did not abolish their discrimination between looming and stationary prepulse stimuli. This suggests that isolation rearing compromised their assessment of potential threats from approaching objects and receding objects.